Immuno stimulant activity of Heterostemma tanjorense (Wight & Arn) on azathioprine induced male albino rats - S. Manikandaselvi, A. R. Angumeenal, S. Thilagam, V. Poornima, R. Thinagarbabu (Journal of Applied Pharmaceutical Science, 2015)
Immunostimulators are substances that stimulate the immune system by increasing the activity of any of its individual component biological systems. The selected plant species Heterostemma tanjorense Wight & Arn is an area specific medicinal plant. Literature review made on this species reveals not much of its medicinal activity to be explored and documented. The present study reports the immune stimulant activity of Heterostemma tanjorense on azathioprine administered male albino rats. Biological parameters such as RBC, WBC, neutrophils, neutrophil adhesive and immunoglobulins were evaluated and the results were reported.The results obtained were in significant quantities and in reportable amounts.
Keywords: Immunostimulant, Heterostemma tanjorense, Immunoglobulins, Immune system, Azathioprine.